Analysis of CXCL9, PD1 and PD-L1 mRNA in stage T1 non-muscle invasive bladder cancer and their association with prognosis - Kubon, Jennifer; Sikic, Danijel; Eckstein, Markus; Weyerer, Veronika; Stöhr, Robert; Neumann, Angela; Keck, Bastian; Wullich, Bernd; Hartmann, Arndt; Wirtz, Ralph M.; Taubert, Helge; Wach, Sven (Cancers, 2020)
Non-muscle invasive bladder cancer (NMIBC), which is characterized by a recurrence rate of approximately 30% and very long treatment times, remains a major unresolved problem for patients and the health care system. The immunological interplay between tumor cells and the immune environment is important for tumor development. Therefore, we analyzed the mRNA of three immune markers, CXCL9, PD1 and PD-L1, in NMIBC by qRT-PCR. The results were subsequently correlated with clinicopathological parameters and prognostic data. Altogether, as expected, higher age was an independent prognostic factor for overall survival (OS) and disease-specific survival (DSS), but not for recurrence-free survival (RFS). Lower CXCL9 mRNA was observed in multivariate Cox’s regression analysis to be an independent prognostic parameter for reduced OS (relative risk; RR = 2.08; p = 0.049), DSS (RR = 4.49; p = 0.006) and RFS (RR = 2.69; p = 0.005). In addition, PD-L1 mRNA was an independent prognostic factor for DSS (RR = 5.02; p = 0.042) and RFS (RR = 2.07; p = 0.044). Moreover, in univariate Cox’s regression analysis, the stratification of patients revealed that low CXCL9 or low PD1 mRNA was associated with reduced RFS in the younger patient group (≤71 years), but not in the older patient group (>71 years). In addition, low CXCL9 or low PD-L1 was associated with shorter RFS in patients with higher tumor cell proliferation and in patients without instillation therapy. In conclusion, the characterization of mRNA levels of immune markers differentiates NIMBC patients with respect to prognosis.
CRIS-Team Scopus Importer:2020-10-09
Keywords: CXCL9; PD-L1; PD1; Prognosis; Stage T1 NMIBC